Autonomy of High-Risk Pregnant Women in an Effort to Prevent Complications during Childbirth - Nafikadini, Iken; Anggi Eka Septiani; Ragil Ismi Hartanti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Maternal mortality is a health problem that has not been resolved until now. Based on data from January-September 2020 from the Public Health Center of Panti District, most pregnant women with high risk are those who have a risk of preeclampsia. Pregnant women have an important role and personal autonomy in decision-making during the process of pregnancy. Objective: To analyze the autonomy of high-risk pregnant women to prevent complications during childbirth. Methods: Qualitative research with a case study approach. Determination of the main informants using a purposive technique consisted of five pregnant women at risk of preeclampsia who were under 20 years old and above 35 years old. Data collection using in-depth interview guide and documentation. Data analysis using inductive thematic analysis. Results: intentions, affordability of information, situations in preparing blood donors, and maternity funds can form the negative autonomy of high-risk pregnant women in decision-making. Husband's social support can form positive autonomy of high-risk pregnant women in decision making. High-risk pregnant women have negative autonomy in choosing a place for maternity care to practice as a midwife even though they have been advised to carry out routine checks at the primary healthcare. High-risk pregnant women have negative autonomy in choosing the place of delivery by not changing their choice and making the primary healthcare or hospital the second and last choice. Conclusion: The autonomy of high-risk pregnant women has formed a negative autonomy in making decisions about childbirth planning and preventing complications.